GE_GERICHTE P/11416/2018 vom 12. Juli 2019 - GE Cour de justice (2019)
ERREUR DE DROIT(DROIT PÉNAL) ; ERREUR SUR LES FAITS(DROIT PÉNAL) ; DOL ÉVENTUEL ; FIXATION DE LA PEINE ; PEINE PÉCUNIAIRE | LEI.115.al1.letb; cp.21; cp.13; cp.12.al3; cp.47; cp.34.al1